2012
DOI: 10.1002/pc.22280
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, mechanical, and thermal characterization of biopolymer composites based on polylactide and nanographite platelets

Abstract: This work focuses on development and optimization of polylactide (PLA) and nanographite platelets (NGP) based composites to display possible superior mechanical and improved thermal stability. Melt blending and dry mixing methods of fabrication were employed at temperature of 180°C. Different Loading fractions of NGP were incorporated into polymer matrix. Morphological evaluation techniques such as XRD and TEM were applied to determine the degree of dispersion of NGPs into PLA matrix. Mechanical properties wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 39 publications
4
43
0
Order By: Relevance
“…A steady transformation from linear to nonlinear behavior occurred at strain ≈10; hence, in order to calculate the damping functions of the samples, the nonlinear stress relaxation measurements were conducted at strain magnitudes above 10. The formation of the percolation network of the NGPs within PLA matrix at 180 °C was methodically studied by the authors in earlier publications . Briefly, the percolation threshold of the samples (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A steady transformation from linear to nonlinear behavior occurred at strain ≈10; hence, in order to calculate the damping functions of the samples, the nonlinear stress relaxation measurements were conducted at strain magnitudes above 10. The formation of the percolation network of the NGPs within PLA matrix at 180 °C was methodically studied by the authors in earlier publications . Briefly, the percolation threshold of the samples (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The authors have already reported the morphological, thermal, mechanical and shear rheological characterizations of the samples . Figure illustrates the transmission electron microscopy (TEM) of PLA/NGP composites of this study, which were comprehensively investigated and reported elsewhere .…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations